Upregulation of Cysteine Protease Cathepsin X in the 6-Hydroxydopamine Model of Parkinson’s Disease - Pišlar, Anja; Tratnjek, Larisa; Glavan, Gordana; Živin, Marko; Kos, Janko (Frontiers in Molecular Neuroscience, 2018)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by loss of midbrain dopaminergic neurons in the substantia nigra compacta (SNc). In vitro, a contribution to neuroinflammation and neurotoxicity has been shown for the lysosomal protease cathepsin X; however, its expression and its role in PD remain unknown. Therefore, the current study was designed to address the regional, cellular and subcellular localization and activity of cathepsin X in hemi-parkinsonian rats with 6-hydroxydopamine (6-OHDA)-induced excitotoxicity in the unilateral medial forebrain bundle (MFB) lesion. We report for the first time that cathepsin X expression and activity are rapidly increased in the ipsilateral SNc after injection of 6-OHDA into the MFB reaching a maximum after 12 h but seem to stay strongly upregulated after 4 weeks after injection. At early time points of 6-OHDA injection into the MFB, the increased cathepsin X is localized in the lysosomes in the neuronal, predominantly tyrosine hydroxylase-positive dopaminergic cells. After 12 h of 6-OHDA induced lesion, only a few activated microglial cells are positive for cathepsin X whereas, in 4 weeks post-lesion accompanied with complete loss of dopaminergic neurons, there is persistent cathepsin X upregulation restricted to activated glia cells. Taken together, our results demonstrate that cathepsin X upregulation in the lesioned dopaminergic system may play a role as a pathogenic factor in PD. Moreover, inhibition of cathepsin X expression or activity may be useful in protecting the nigrostriatal dopaminergic projection in the PD.